2021
DOI: 10.7717/peerj.11964
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the lignin toolbox formorusand the roles of lignin related genes in response to zinc stress

Abstract: Mulberry (Morus, Moraceae) is an important economic plant with nutritional, medicinal, and ecological values. Lignin in mulberry can affect the quality of forage and the saccharification efficiency of mulberry twigs. The availability of the Morus notabilis genome makes it possible to perform a systematic analysis of the genes encoding the 11 protein families specific to the lignin branch of the phenylpropanoid pathway, providing the core genes for the lignin toolbox in mulberry. We performed genome-wide screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Liu et al (2015) observed that the up-regulation of PAL and 4CL gene expression in rice roots was responsible for the elevation of lignin content with increasing Cu concentration. In addition, high expression of 4CL and CAD genes was related to the ligni cation in morus under excess Zn stress (Chao et al 2021). The present data indicated that Fe-induced signi cant increases of PAL, 4CL and CAD activities (Fig.…”
Section: Effects Of Different Treatments On Cw-bound Gpx and Capx Act...mentioning
confidence: 99%
“…Liu et al (2015) observed that the up-regulation of PAL and 4CL gene expression in rice roots was responsible for the elevation of lignin content with increasing Cu concentration. In addition, high expression of 4CL and CAD genes was related to the ligni cation in morus under excess Zn stress (Chao et al 2021). The present data indicated that Fe-induced signi cant increases of PAL, 4CL and CAD activities (Fig.…”
Section: Effects Of Different Treatments On Cw-bound Gpx and Capx Act...mentioning
confidence: 99%
“…Among them, CCR catalyzes the coumarin production, plays an important role in regulating the carbon flow of lignin biosynthesis pathway. In total, we found 31 CCR homology genes in lacquer genome, while 31 are present in pear ( Pyrus bretschneideri ) ( Cheng et al., 2017 ), 14 are present in soybean ( Cui et al., 2021 ), and six are present in mulberry ( Chao et al., 2021 ). The TvCCR phylogenetic tree constructed with CCRs from Arabidopsis thaliana , O. sativa , Populus , as well as P. vera and S. birrea revealed that CCRs are clustered into four groups ( Figure S12 ), which indicated that CCRs had structural and functional divergence.…”
Section: Resultsmentioning
confidence: 98%
“…Our previous reported RAN-seq data (Accession number: PRJNA660559) was used to obtain the expression profiles of R2R3 and 3R - MaMYB s in roots, stems and leaves [ 31 ]. Expression profile of R2R3 and 3R-MaMYB s in different fruit development stages was obtained using RNA-seq data with accession number: CRA006074 in national genomics data center (NGDC).…”
Section: Methodsmentioning
confidence: 99%